Perfil semântico dos questionamentos nas aulas de química: uma análise a partir da teoria dos códigos de legitimação - Santos, Myllena dos (2024)
The general aim of this study is to evaluate the relationship between the teacher's communicative approach and the semantic dimension of the questions asked in chemistry lessons. This is a qualitative study, structured in multipaper format, which is organized into three articles. The first article is a documentary study, the second is a theoretical essay and the third is an empirical study. Each comprises specific objectives and are independent of each other, while at the same time being connected to each other in order to achieve the general objective of this study. Based on the results obtained in the Systematic Literature Review (Article 1), two translation devices were constructed to analyse the semantic dimension of the questions (Article 2) in order to categorize the lessons of two high school chemistry teachers from the public school system in the state of Sergipe (Article 3). The lessons were recorded, transcribed and analyzed using the concepts of gravity and semantic density from the Theory of Legitimation Codes (LCT). In addition, the analysis episodes were also categorized using Mortimer and Scott's (2002) notion of communicative approach. The results show that the predominant types of questioning in the teachers' classes are those of a low and medium cognitive level, and only in teacher Bárbara's classes was there an incidence of high cognitive level questioning. With regard to the communicative approach, there was a predominance of interactive/authoritative discourse for teacher Aurora and interactive/dialogical discourse for teacher Bárbara. Based on the results, it was possible to conclude that the questions about more abstract chemical concepts - those present at level 4 of semantic severity - are characteristic of the interactive/authoritative communicative approach, which integrates the questions that seek to arrive at the scientific point of view. Given the above, the importance of varying questioning in the classroom is highlighted, as well as the transition between the four types of communicative approach. In addition, it has been shown that the analytical tools developed in this research make it possible to analyze and reflect on teaching practices regarding the types of questioning adopted in the chemistry classroom, seeking to improve pedagogical practices with the aim of improving the teaching and learning process.